VERBAL INTERACTIONS IN EFL AT THE SENIOR VOCATIONAL HIGH SCHOOL - Ristyananda, I. P; Tantra, D.K; Mahendrayana, G (Journal of Education Research and Evaluation, 2020)
This study was focused on identifying, classifying and understanding speech acts produced by teachers and tenth-grade students of Senior Vocational High School.  The study was focused on locutionary acts, illocutionary acts, and perlocutionary produced during the EFL learning process under the theory of Austin (1962) and the theory of Searle (1969). Descriptive Qualitative design was employed in this study. Two teachers and sixty students of SMK Negeri 3 Singaraja were chosen as the sample in this study. The data were gathered through observation assisted by video recorder. The data were analyzed descriptive-qualitatively. The result of the study showed that the teachers produced all types of speech acts, namely directive, commisive, expressive, declarative and assertive. The most dominant type produced was directive act in form of requesting. It was used to ask the students for doing something and giving instruction. The other types of speech acts were not dominant. Meanwhile, the students produced three types of speech acts, namely directive, expressive, and assertive. The most dominant type produced was directive act in form of requesting through asking question and telling, through telling their daily routine. Meanwhile Expressive act in form of welcoming through greeting the teacher and assertive in form of describing through describe their friends, parents, and teachers. In additions, it was shown that the teachers produced more speech acts than the students, and the entire locutionary acts produced were understood by the interlocutors, it can be seen from appropriate respond performed.